Discovery and molecular interaction studies of a highly stable, tarantula peptide modulator of acid-sensing ion channel 1. (December 2017) - Er, Sing Yan; Cristofori-Armstrong, Ben; Escoubas, Pierre; Rash, Lachlan D.
Abstract: Acute pharmacological inhibition of acid-sensing ion channel 1a (ASIC1a) is efficacious in rodent models in alleviating symptoms of neurological diseases such as stroke and multiple sclerosis. Thus, ASIC1a is a promising therapeutic target and selective ligands that modulate it are invaluable research tools and potential therapeutic leads. Spider venoms have provided an abundance of voltage-gated ion channel modulators, however, only one ASIC modulator (PcTx1) has so far been isolated from this source. Here we report the discovery, characterization, and chemical stability of a second spider venom peptide that potently modulates ASIC1a and ASIC1b, and investigate the molecular basis for its subtype selectivity. π-TRTX-Hm3a (Hm3a) is a 37-amino acid peptide isolated from Togo starburst tarantula ( Heteroscodra maculata ) venom with five amino acid substitutions compared to PcTx1, and is also three residues shorter at the C-terminus. Hm3a pH-dependently inhibited ASIC1a with an IC50 of 1–2 nM and potentiated ASIC1b with an EC50 of 46.5 nM, similar to PcTx1. Using ASIC1a to ASIC1b point mutants in rat ASIC1a revealed that Glu177 and Arg175 in the palm region opposite α-helix 5 play an important role in the Hm3a-ASIC1 interaction and contribute to the subtype-dependent effects of the peptide. Despite its high sequence similarity with PcTx1, Hm3a showed higher levels of stability over 48 h. Overall, Hm3a represents a potent, highly stable tool for the study of ASICs and will be particularly useful when stability in biological fluids is required, for example in long term in vitro cell-based assays and in vivo experiments. This article is part of the Special Issue entitled 'Venom-derived Peptides as Pharmacological Tools.' Highlights: Hm3a is an ASIC1 modulating peptide isolated from Togo starburst tarantula venom. Hm3a is a truncated variant of PcTx1 with very similar pharmacological activity. ASIC1a residues E177 and R175 are important for subtype-dependent effects of Hm3a. Hm3a is substantially more biologically stable than PcTx1 over 48 hours.